2012
DOI: 10.1149/2.066211jes
|View full text |Cite
|
Sign up to set email alerts
|

Pulse-Plating of Copper-Silver Alloys for Interconnect Applications

Abstract: The electrodeposition of Cu-Ag alloys was studied as a possible application for interconnect technology, where Cu-Ag alloys may be less susceptible to electromigration than Cu alone. The presence of chloride in state-of-the-art copper plating electrolytes limited the solubility of Ag. However, pulse-plating approach enabled a wide range of Cu-Ag alloy compositions at substantial chloride concentration levels. The deposition of Ag was driven by the displacement reactions between the metallic copper and ionic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…However, alloying normally causes higher electrical resistivity. Fortunately, it is also found that alloying Cu with Ag would cause the increase in the Cu–Ag resistivity the least, when compared to other copper alloys [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, alloying normally causes higher electrical resistivity. Fortunately, it is also found that alloying Cu with Ag would cause the increase in the Cu–Ag resistivity the least, when compared to other copper alloys [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to circumvent the precipitation issue of AgCl in this methanesulfonic acid bath, thiourea (TU) was adopted as a chelating agent in the electroplating bath. 21 Since the concentration of Ag ion in the electrolyte should be one of the key factors in controlling the composition of Cu-Ag deposits, [22][23][24][25] silver ions in various concentrations were added into the methanesulfonic acid copper electrolyte to extend the composition of Cu-Ag deposits. Meanwhile, several concentration ratios between TU and Ag + (denoted as [TU]/[Ag + ]) were set to evaluate the effect of TU on the microstructure and composition of Cu-Ag deposits.…”
Section: Resultsmentioning
confidence: 99%
“…31 In some of these studies, the elemental composition and total deposited amounts were calculated by removing the working electrode from the cell, and stripping off the deposited layer ex situ to analyze it through ICP-MS or ICP-OES. 25,27,29,32 Alternatively, metal recovery calculations were performed by analyzing the solution with ICP-MS before and after EDRR. 26 Static EQCM cells have also been used in EDRR and surface limited redox replacement (SLRR) studies to describe the electric potential and mass transients involved in deposition and redox replacement processes.…”
Section: Cementioning
confidence: 99%